Screening-detected positive serology for celiac disease: a real clinical challenge. Issue Volume 33:Issue S1(2021) (19th February 2021) - Donat, Ester; Roca, Maria; Masip, Etna; Polo, Begoña; Ramos, David; Ribes-Koninckx, Carmen
Abstract : According to European Society for Paediatric Gastroenterology, Hepatology, and Nutrition 2020 criteria for celiac disease diagnosis, the small bowel biopsy (SBB) can be omitted in selected circumstances, even in asymptomatic patients. Hence, we have conducted a retrospective study to identify the histological findings of the asymptomatic patients with antitransglutaminase IgA antibodies 10 times above the upper limit of normal and positive antiendomisium antibodies; 5/24 patients fulfilling these criteria had, however, a nonconclusive SBB and were diagnosed with potential celiac disease. The nonbiopsy approach in these cases needs to be carefully evaluated and the risk of overdiagnosis pondered as the management and evolution of potential celiac disease cases is still a matter of study.